2018
DOI: 10.1177/1049731518779440
|View full text |Cite
|
Sign up to set email alerts
|

The Hong Kong Statement on Practice Research 2017: Contexts and Challenges of the Far East

Abstract: This statement on social work practice research highlights the contributions of scholars, practitioners, and conference participants in the Fourth International Conference on Practice Research (ICPR) in 2017, hosted by The Hong Kong Polytechnic University in May 2017. It focuses on the contexts and challenges of carrying out practice research in the Far East and beyond as well as raises pertinent questions about the development of practice research. It begins with a brief description of the context of social w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…The definition of social work practice research is evolving. This study adopts the definition recently used by Dodd and Epstein (2012), Epstein (2001), and the Second International Conference on Practice Research Scientific Committee (Helsinki Forum Group, 2014) and also found in the Salisbury Statement of 2008 (The Salisbury Forum Group, 2011), the New York Statement of 2014 (Epstein et al, 2015), and the Hong Kong Statement of 2017 (Sim et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The definition of social work practice research is evolving. This study adopts the definition recently used by Dodd and Epstein (2012), Epstein (2001), and the Second International Conference on Practice Research Scientific Committee (Helsinki Forum Group, 2014) and also found in the Salisbury Statement of 2008 (The Salisbury Forum Group, 2011), the New York Statement of 2014 (Epstein et al, 2015), and the Hong Kong Statement of 2017 (Sim et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Joubert and Hocking (2015) developed a systemic model that encouraged social workers to participate in “evidence-informed” practice research. The unique context of each country and territory, whether its socioeconomic characteristics or the stage it has reached in social work development, has also emerged as an important consideration in the development of practice research in social work (Sim et al, 2019; Sim, 2016).…”
Section: The Global Development Of Social Work Practice Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Er wordt niet gerefereerd aan de eventuele betekenis voor beroepsopleidingen. Het in praktijk vormgeven aan deze uitgangspunten staat in de kinderschoenen (Austin, Fisher, & Uggerhoj, 2014) en leidt tot nieuwe aandachtspunten en vragen (Sim et al, 2018).…”
Section: Werkplaatsen Als Ruimten Voor Kennisproductie Onderwijs En unclassified
“…This special issue, "Practice Research in Chinese Societies", emanates from and adds to the dialogues and debates from the Fourth International Conference on Practice Research (ICPR) that was hosted by the Hong Kong Polytechnic University in May 2017 (Sim 2016;Sim et al 2018).…”
Section: Dialogues and Debates In Practice Researchmentioning
confidence: 99%